Perubahan Perilaku Masyarakat Kumuh Perkotaan Melalui Program Kota Tanpa Kumuh - Mutia Nur Ilmi; Firdaus W. Suhaeb (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This research aims to find out: How people's urban behavior has changed through the implementation of the City Without Slums (KOTAKU) program in Tallo Village, Makassar City. This research uses a qualitative method with a descriptive approach. The number of informants in this research was 9 people who were determined using a Purposive Sampling technique with the criteria 1) Tallo Village residents who had lived for at least the last ten years who felt the impact of the slums of surrounding organizations, 2) Tallo Village community institutions. The data collection techniques used in this research are observation, interviews and documentation methods. The three-step qualitative data analysis technique includes data reduction, data presentation, and drawing conclusions. The results of this research show that: changes in urban community behavior that have emerged through the City Without Slums (KOTAKU) program in Tallo Village, Makassar City take three forms, namely cognitive changes, affective changes, and psychomotor changes.